Integrated in vitro/in silico test battery for the prediction of chemical-induced cholestatic liver toxicity - Annika Drees; Emilio Benfenati; Domenico Gadaleta; Rafael Gozalbes; Marina Garcia de Lomana; Jian Jiang; Amy Maerten; Rita Ortega-Vallbona; Eva Serrano-Candelas; Julen Sanz-Serrano; Mathieu Vinken (Toxicology, 2026)

Advancing toxicology through new approach methodologies - Mathieu Vinken (Toxicology, 2026)

Insights into tartrazine-exposure and potential hepatotoxicity - Ellen Callewaert; Jochem Louisse; Nynke Kramer; Mathieu Vinken (Chemico-Biological Interactions, 2026)

A study of liver toxicity within harmonised classifications under REACH - Annika Drees; Mathieu Vinken; Julen Sanz-Serrano (Regulatory Toxicology and Pharmacology, 2026)

A combined in silico and in vitro new approach methodology for early detection of liver steatogenic chemicals - Anouk Verhoeven; Domenico Gadaleta; Nisreen H.K. Isbaita; Jian Jiang; Julen Sanz-Serrano; Eva Serrano-Candelas; Rita Ortega-Vallbona; Tamara Vanhaecke; Mathieu Vinken (Chemico-Biological Interactions, 2026)

Mapping 3Rs and NAM research and innovation projects funded through European framework programmes since 2007 - Julia Matyjasiak; Alexandra-Costina Avîrvarei; Marie Corradi; Amy Maerten; Christian Desaintes; Julen Sanz-Serrano; Mathieu Vinken (Archives of Toxicology, 2026)

Transcriptomic responses to repeated exposure of human C3A liver spheroids to polystyrene nanoplastics - Kyriaki Xiftou; Jian Jiang; Florian Caiment; Theo M. de Kok; Mathieu Vinken; Julen Sanz-Serrano; Andres Tabernilla (Archives of Toxicology, 2026)

From in vitro to in vacuo: a call for space toxicology research - Ben Cools; Mathieu Vinken (Toxicology, 2026)

Mechanism-based new approach methodologies for in vitro detection of chemical-induced liver steatosis - Anouk Verhoeven; Julen Sanz-Serrano; Mathieu Vinken (Archives of Toxicology, 2026)

Mapping the ethical and sustainable transition in toxicology: a bibliometric analysis and a review of new approach methodologies - Ruxandra Malina Petrescu-Mag; Mathieu Vinken; Dacinia Crina Petrescu (Archives of Toxicology, 2026)
Toxicology is undergoing a paradigm shift, driven by the ethical imperative to reduce animal testing, the pursuit of sustainability, and regulatory transitions toward new approach methodologies (NAMs). This study systematically maps the integration of ethics and sustainability into NAMs-related toxicological research, using a mixed-methods design that combines bibliometric analysis with a review of scientific and policy literature. Our findings reveal a steep increase in NAMs publications since 2015, with in vitro and in silico approaches at the forefront. Bibliometric clustering identified three dominant thematic domains—regulatory testing, methodological performance factors, and human cell culture innovation—each reflecting varying degrees of engagement with ethical, scientific, and sustainability principles. A qualitative matrix was also developed to link the bibliometric clusters to key ethical and methodological dimensions, highlighting the growing centrality of themes such as the 3Rs, sustainability, and regulatory reform. Notably, the scientific and political discourse is shifting from merely “symbolic” ethics, used primarily to signal alignment with funding priorities or public expectations, toward more deeply embedded and actionable ethical frameworks. Initiatives emphasize operational ethics through concepts such as the fourth R (responsibility), with more expanded models including 12Rs, the 3C model (cell culture, computer simulation, and clinical trials), and ethics-driven AI tools. These developments signal a maturing field where ethics is becoming a methodological imperative. By mapping these shifts, the study offers an integrated perspective on how ethical values shape scientific innovation in toxicology. It provides evidence-based directions for accelerating a responsible transition to animal-free, human-relevant, and resource-efficient risk assessment.

A mechanistically-anchored and human stem cell-based in vitro test battery for assessing liver steatogenic potential of chemicals - Anouk Verhoeven; Alexandra Gatzios; Robim M. Rodrigues; Julen Sanz-Serrano; Joery De Kock; Mathieu Vinken; Tamara Vanhaecke (Toxicology, 2025)

Effects of per- and polyfluoroalkyl substances on molecular initiating events of cholestatic liver injury - Amy Maerten; Ellen Callewaert; Julen Sanz-Serrano; Lindsey Devisscher; Mathieu Vinken (Science of The Total Environment, 2025)

In vitro test battery for testing molecular initiating events in chemical-induced cholestasis - Amy Maerten; Annika Drees; Jian Jiang; Julen Sanz-Serrano; Lindsey Devisscher; Mathieu Vinken (Toxicology, 2025)

The brain-eye-liver axis during spaceflight: implications of hepatic dysfunction in spaceflight associated neuro-ocular syndrome - Sinem Helvacıoğlu Akyüz; Ben Cools; Joshua Ong; Ethan Waisberg; Ryung Lee; Andrew G. Lee; Mathieu Vinken (Life Sciences in Space Research, 2025)

Bridging dimensions: a comparative analysis of 2D and 3D in vitro models for hepatocellular carcinoma research - Leticia C. Valente; Luana Riechelman-Casarin; Laura L. P. Esteves; Gabriel P. Bacil; Tereza Cristina da Silva; Mathieu Vinken; Bruno Cogliati; Scott L. Friedman; Amedeo Columbano; Luís Fernando Barbisan; Guilherme R. Romualdo (Archives of Toxicology, 2025)

Nanobody-based Pannexin1 channel inhibitors increase survival after cardiac ischemia/reperfusion - Olga M. Rusiecka; Filippo Molica; Linda Clochard; Raf Van Campenhout; Timo W. M. De Groof; Viviane Bes; Nick Devoogdt; Serge Muyldermans; Mathieu Vinken; Brenda R. Kwak (Cell and Tissue Research, 2025)
Reperfusion following myocardial infarction salvages the ischemic heart but paradoxically exacerbates injury. Yet, efficient treatment for cardiac ischemia/reperfusion injury is still missing in clinics. ATP release through Pannexin1 (PANX1) channels facilitates recruitment of leukocytes to the injured myocardium. Thus, PANX1 channel inhibition might confer cardioprotection. Currently available PANX1 channel blockers lack specificity or in vivo stability. Nanobodies offer a new therapeutic modality given their high target affinity, small size, and deep tissue penetration. Nanobodies targeting Panx1 were recently introduced. Here, their target specificity and selective PANX1 channel inhibition for cardiovascular purposes were validated in vitro. The two most promising candidates were further examined in the context of cardiac ischemia/reperfusion injury. Nanobody-1 (Nb1) and Nb9 reduced neutrophil adhesion to an endothelial monolayer. Nb1 did not affect left ventricular function ex vivo; however, Nb9 tended to diminish the performance of isolated hearts. Finally, in vivo application of Nb1, but not of Nb9 or a control Nb, at the onset of reperfusion increased the survival rate of mice. However, the infarct size observed after treatment with Nb1 was similar than the one found after treatment with the control Nb. In conclusion, Nb1 efficiently and specifically inhibits ATP release from endothelial cells thereby limiting leukocyte adhesion and improving the outcome of cardiac ischemia/reperfusion in mice. This warrants further studies to unveil the detailed molecular mechanism underlying the beneficial effects of Nb1.

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Reproductive Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Regulatory Toxicology and Pharmacology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Food and Chemical Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Chemico-Biological Interactions, 2025)

Tiny molecules, big concerns: ultrashort-chain PFAS on the regulatory radar - Amy Maerten; Julen Sanz-Serrano; Lindsey Devisscher; Mathieu Vinken (Archives of Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Toxicology Letters, 2025)

Optimization of the drug-induced cholestasis index based on advanced modeling for predicting liver toxicity - Annika Drees; Vahid Nassiri; Andrés Tabernilla; Jan Serroyen; Emmanuel Gustin; Bruna dos Santos Rodrigues; Darren Michael Moss; Ann De Smedt; Mathieu Vinken; Freddy Van Goethem; Julen Sanz-Serrano (Toxicology, 2025)

The Alarming Consequences of Workforce Reductions at the FDA, EPA, NIH and CDC in the United States - Martin van den Berg; Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael D. Coleman; Mark T.D. Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew C. Wright (Environmental Toxicology and Pharmacology, 2025)

The alarming consequences of workforce reductions at the FDA, EPA, NIH and CDC in the United States - Daniel R. Dietrich; Sonja von Aulock; Anna Bal-Price; Michael Coleman; Mark Cronin; Paul Jennings; Angela Mally; Mathieu Vinken; Matthew Wright; Martin van den Berg (Archives of Toxicology, 2025)

Effects of per- and polyfluoroalkyl substances on the liver: Human-relevant mechanisms of toxicity - Amy Maerten; Ellen Callewaert; Julen Sanz-Serrano; Lindsey Devisscher; Mathieu Vinken (Science of The Total Environment, 2024)

Investigation of parenteral nutrition-induced hepatotoxicity using human liver spheroid co-cultures - Milos Mihajlovic; Sybren De Boever; Andrés Tabernilla; Ellen Callewaert; Julen Sanz-Serrano; Anouk Verhoeven; Amy Maerten; Zenzi Rosseel; Elisabeth De Waele; Mathieu Vinken (Archives of Toxicology, 2024)
Parenteral nutrition (PN) is typically administered to individuals with gastrointestinal dysfunction, a contraindication for enteral feeding, and a need for nutritional therapy. When PN is the only energy source in patients, it is defined as total parenteral nutrition (TPN). TPN is a life-saving approach for different patient populations, both in infants and adults. However, despite numerous benefits, TPN can cause adverse effects, including metabolic disorders and liver injury. TPN-associated liver injury, known as intestinal failure-associated liver disease (IFALD), represents a significant problem affecting up to 90% of individuals receiving TPN. IFALD pathogenesis is complex, depending on the TPN components as well as on the patient’s medical conditions. Despite numerous animal studies and clinical observations, the molecular mechanisms driving IFALD remain largely unknown. The present study was set up to elucidate the mechanisms underlying IFALD. For this purpose, human liver spheroid co-cultures were treated with a TPN mixture, followed by RNA sequencing analysis. Subsequently, following exposure to TPN and its single nutritional components, several key events of liver injury, including mitochondrial dysfunction, endoplasmic reticulum stress, oxidative stress, apoptosis, and lipid accumulation (steatosis), were studied using various techniques. It was found that prolonged exposure to TPN substantially changes the transcriptome profile of liver spheroids and affects multiple metabolic and signaling pathways contributing to liver injury. Moreover, TPN and its main components, especially lipid emulsion, induce changes in all key events measured and trigger steatosis.

Accessible methods and tools to estimate chemical exposure in humans to support risk assessment: A systematic scoping review - Maria E. Kalyva; Gunn E. Vist; Michael Guy Diemar; Graciela López-Soop; T.J. Bozada; Thomas Luechtefeld; Erwin L. Roggen; Hubert Dirven; Mathieu Vinken; Trine Husøy (Environmental Pollution, 2024)

A quantitative weight-of-evidence method for confidence assessment of adverse outcome pathway networks: A case study on chemical-induced liver steatosis - Anouk Verhoeven; Jonas van Ertvelde; Joost Boeckmans; Alexandra Gatzios; Ramiro Jover; Birgitte Lindeman; Graciela Lopez-Soop; Robim M. Rodrigues; Anna Rapisarda; Julen Sanz-Serrano; Marth Stinckens; Sara Sepehri; et al. (Toxicology, 2024)

Unraveling the micro- and nanoplastic predicament: A human-centric insight - Sybren De Boever; Lindsey Devisscher; Mathieu Vinken (Science of The Total Environment, 2024)

Effects of glyphosate exposure on western diet-induced non-alcoholic fatty liver disease in mice - Guilherme R. Romualdo; Letícia Cardoso Valente; Ana Carolina Sprocatti dos Santos; Núbia Alves Grandini; Camila Renata Correa Camacho; Mathieu Vinken; Bruno Cogliati; De-Xing Hou; Luís Fernando Barbisan (Environmental Toxicology and Pharmacology, 2023)

Unraveling the mechanisms underlying drug-induced cholestatic liver injury: identifying key genes using machine learning techniques on human in vitro data sets - Jian Jiang; Jonas van Ertvelde; Gökhan Ertaylan; Ralf Peeters; Danyel Jennen; Theo M. de Kok; Mathieu Vinken (Archives of Toxicology, 2023)
Drug-induced intrahepatic cholestasis (DIC) is a main type of hepatic toxicity that is challenging to predict in early drug development stages. Preclinical animal studies often fail to detect DIC in humans. In vitro toxicogenomics assays using human liver cells have become a practical approach to predict human-relevant DIC. The present study was set up to identify transcriptomic signatures of DIC by applying machine learning algorithms to the Open TG-GATEs database. A total of nine DIC compounds and nine non-DIC compounds were selected, and supervised classification algorithms were applied to develop prediction models using differentially expressed features. Feature selection techniques identified 13 genes that achieved optimal prediction performance using logistic regression combined with a sequential backward selection method. The internal validation of the best-performing model showed accuracy of 0.958, sensitivity of 0.941, specificity of 0.978, and F1-score of 0.956. Applying the model to an external validation set resulted in an average prediction accuracy of 0.71. The identified genes were mechanistically linked to the adverse outcome pathway network of DIC, providing insights into cellular and molecular processes during response to chemical toxicity. Our findings provide valuable insights into toxicological responses and enhance the predictive accuracy of DIC prediction, thereby advancing the application of transcriptome profiling in designing new approach methodologies for hazard identification.

Evaluation of functional candidate biomarkers of non-genotoxic hepatocarcinogenicity in human liver spheroid co-cultures - Bruna dos Santos Rodrigues; Kaat Leroy; Milos Mihajlovic; Sybren De Boever; Sarah Vanbellingen; Bruno Cogliati; Joeri L. Aerts; Mathieu Vinken (Archives of Toxicology, 2023)

Correction to: Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2022)

Hepatotoxicity induced by nanomaterials: mechanisms and in vitro models - Vânia Vilas-Boas; Mathieu Vinken (Archives of Toxicology, 2021)

Screening of repeated dose toxicity data in safety evaluation reports of cosmetic ingredients issued by the Scientific Committee on Consumer Safety between 2009 and 2019 - Emma Gustafson; Christophe Debruyne; Olga De Troyer; Vera Rogiers; Mathieu Vinken; Tamara Vanhaecke (Archives of Toxicology, 2020)
A focal point in the safety evaluation of cosmetic ingredients includes oral repeated dose toxicity testing, which is intended to address the most complex human endpoints. Seven years after the full implementation of the animal testing ban for cosmetic ingredients in the EU, there are still no alternative methods available capable of fully replacing oral repeated dose toxicity testing. Until this issue is resolved, the development of new cosmetic ingredients remains seriously hampered. The present paper describes a thorough screening of the oral repeated dose toxicity data included in safety evaluation reports of cosmetic ingredients addressed in the Annexes of the Cosmetics Regulation (EC) No 1223/2009, issued by the Scientific Committee on Consumer Safety between 2009 and 2019. The liver and the haematological system were identified as the potentially most frequently affected organs upon oral administration of cosmetic ingredients to animals. Evaluation of altered biochemical, morphological, and histopathological parameters related to hepatotoxicity indicated that the most recurrent events are liver weight changes, elevated liver enzymes, and alterations in serum cholesterol and bilirubin levels. Combined listing of affected parameters associated with steatosis and cholestasis indicated the possible occurrence of cholestasis, provoked by a limited number of cosmetic ingredients. The most frequently affected parameters related to the haematological system were indicative of anaemia. An in-depth analysis allowed characterisation of both regenerative and non-regenerative anaemia, pointing to direct and indirect haematotoxicity, respectively. The results presented in this study call for prioritisation of research targeted towards the development of new approach methodologies fit for animal-free repeated dose toxicity evaluation of cosmetic ingredients.

A putative AOP for pneumonia related to COVID-19 - Mathieu Vinken (Archives of Toxicology, 2020)

Robustness testing and optimization of an adverse outcome pathway on cholestatic liver injury - Eva Gijbels; Vânia Vilas‐Boas; Pieter Annaert; Tamara Vanhaecke; Lindsey Devisscher; Mathieu Vinken (Archives of Toxicology, 2020)

The use of adverse outcome pathways in the safety evaluation of food additives - Mathieu Vinken; Nynke Kramer; Timothy E. H. Allen; Yvette Hoffmans; Natalie Thatcher; Sara Levorato; Heinz Traussnig; Stefan Schulte; Alan Boobis; Anette Thiel; Ivonne M. C. M. Rietjens (Archives of Toxicology, 2020)
In the last decade, adverse outcome pathways have been introduced in the fields of toxicology and risk assessment of chemicals as pragmatic tools with broad application potential. While their use in the pharmaceutical and cosmetics sectors has been well documented, their application in the food area remains largely unexplored. In this respect, an expert group of the International Life Sciences Institute Europe has recently explored the use of adverse outcome pathways in the safety evaluation of food additives. A key activity was the organization of a workshop, gathering delegates from the regulatory, industrial and academic areas, to discuss the potentials and challenges related to the application of adverse outcome pathways in the safety assessment of food additives. The present paper describes the outcome of this workshop followed by a number of critical considerations and perspectives defined by the International Life Sciences Institute Europe expert group.

Characterizing the coverage of critical effects relevant in the safety evaluation of food additives by AOPs - Nynke I. Kramer; Yvette Hoffmans; Siyao Wu; Anette Thiel; Natalie Thatcher; Timothy E. H. Allen; Sara Levorato; Heinz Traussnig; Stefan Schulte; Alan Boobis; Ivonne M. C. M. Rietjens; Mathieu Vinken (Archives of Toxicology, 2019)

Key performance indicators of the contemporary European academic toxicologist - Mathieu Vinken; Heather M. Wallace (Archives of Toxicology, 2019)

Mechanisms and in vitro models of drug-induced cholestasis - Eva Gijbels; Vânia Vilas-Boas; Neel Deferm; Lindsey Devisscher; Hartmut Jaeschke; Pieter Annaert; Mathieu Vinken (Archives of Toxicology, 2019)

Characterization of hepatocyte-based in vitro systems for reliable toxicity testing - Mathieu Vinken; Jan G. Hengstler (Archives of Toxicology, 2018)

Comparison of base-line and chemical-induced transcriptomic responses in HepaRG and RPTEC/TERT1 cells using TempO-Seq - Alice Limonciel; Gamze Ates; Giada Carta; Anja Wilmes; Manfred Watzele; Peter J. Shepard; Harper C. VanSteenhouse; Bruce Seligmann; Joanne M. Yeakley; Bob van de Water; Mathieu Vinken; Paul Jennings (Archives of Toxicology, 2018)

Genetic ablation of pannexin1 counteracts liver fibrosis in a chemical, but not in a surgical mouse model - Sara Crespo Yanguas; Tereza C. da Silva; Isabel V. A. Pereira; Michaël Maes; Joost Willebrords; Valery I. Shestopalov; Bruna M. Goes; Marina Sayuri Nogueira; Inar Alves de Castro; Guilherme R. Romualdo; Luís F. Barbisan; Eva Gijbels; et al. (Archives of Toxicology, 2018)

Omics-based responses induced by bosentan in human hepatoma HepaRG cell cultures - Robim M. Rodrigues; Laxmikanth Kollipara; Umesh Chaudhari; Agapios Sachinidis; René P. Zahedi; Albert Sickmann; Annette Kopp-Schneider; Xiaoqi Jiang; Hector Keun; Jan Hengstler; Marlies Oorts; Pieter Annaert; et al. (Archives of Toxicology, 2018)

In vitro prediction of drug-induced cholestatic liver injury: a challenge for the toxicologist - Mathieu Vinken (Archives of Toxicology, 2018)

Functional cardiotoxicity assessment of cosmetic compounds using human-induced pluripotent stem cell-derived cardiomyocytes - Umesh Chaudhari; Harshal Nemade; Poornima Sureshkumar; Mathieu Vinken; Gamze Ates; Vera Rogiers; Jürgen Hescheler; Jan Georg Hengstler; Agapios Sachinidis (Archives of Toxicology, 2018)

Adverse outcome pathways: opportunities, limitations and open questions - Marcel Leist; Ahmed Ghallab; Rabea Graepel; Rosemarie Marchan; Reham Hassan; Susanne Hougaard Bennekou; Alice Limonciel; Mathieu Vinken; Stefan Schildknecht; Tanja Waldmann; Erik Danen; Ben van Ravenzwaay; et al. (Archives of Toxicology, 2017)

Adverse outcome pathways: a concise introduction for toxicologists - Mathieu Vinken; Dries Knapen; Lucia Vergauwen; Jan G. Hengstler; Michelle Angrish; Maurice Whelan (Archives of Toxicology, 2017)

Erratum to: Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Adverse outcome pathway development from protein alkylation to liver fibrosis - Tomislav Horvat; Brigitte Landesmann; Alfonso Lostia; Mathieu Vinken; Sharon Munn; Maurice Whelan (Archives of Toxicology, 2017)

Connexins, Pannexins, and Their Channels in Fibroproliferative Diseases - Bruno Cogliati; Gregory Mennecier; Joost Willebrords; Tereza Cristina Da Silva; Michaël Maes; Isabel Veloso Alves Pereira; Sara Crespo Yanguas; Francisco Javier Hernandez-Blazquez; Maria Lúcia Zaidan Dagli; Mathieu Vinken (The Journal of Membrane Biology, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Experimental models of liver fibrosis - Sara Crespo Yanguas; Bruno Cogliati; Joost Willebrords; Michaël Maes; Isabelle Colle; Bert van den Bossche; Claudia Pinto Marques Souza de Oliveira; Wellington Andraus; Venâncio Avancini Alves; Isabelle Leclercq; Mathieu Vinken (Archives of Toxicology, 2016)

MicroRNAs as key regulators of xenobiotic biotransformation and drug response - Jennifer Bolleyn; Joery De Kock; Robim Marcelino Rodrigues; Mathieu Vinken; Vera Rogiers; Tamara Vanhaecke (Archives of Toxicology, 2015)

Connexin hemichannels: novel mediators of toxicity - Mathieu Vinken (Archives of Toxicology, 2015)

Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2014)

Primary hepatocytes and their cultures in liver apoptosis research - Mathieu Vinken; Michaël Maes; André G. Oliveira; Bruno Cogliati; Pedro E. Marques; Gustavo B. Menezes; Maria Lúcia Zaidan Dagli; Tamara Vanhaecke; Vera Rogiers (Archives of Toxicology, 2014)

Adverse outcome pathways: hype or hope? - Mathieu Vinken; Maurice Whelan; Vera Rogiers (Archives of Toxicology, 2014)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Proteomic and metabolomic responses to connexin43 silencing in primary hepatocyte cultures - Mathieu Vinken; Michaël Maes; Rachel Cavill; Dirk Valkenborg; James K. Ellis; Elke Decrock; Luc Leybaert; An Staes; Kris Gevaert; André G. Oliveira; Gustavo B. Menezes; Bruno Cogliati; et al. (Archives of Toxicology, 2013)

Comparison of genotoxicant-modified transcriptomic responses in conventional and epigenetically stabilized primary rat hepatocytes with in vivo rat liver data - Tatyana Y. Doktorova; Heidrun Ellinger-Ziegelbauer; Mathieu Vinken; Tamara Vanhaecke; Joost van Delft; Jos Kleinjans; Hans-Juergen Ahr; Vera Rogiers (Archives of Toxicology, 2012)

Comparison of hepatocarcinogen-induced gene expression profiles in conventional primary rat hepatocytes with in vivo rat liver - Tatyana Y. Doktorova; Heidrun Ellinger-Ziegelbauer; Mathieu Vinken; Tamara Vanhaecke; Joost van Delft; Jos Kleinjans; Hans-Juergen Ahr; Vera Rogiers (Archives of Toxicology, 2012)

Screening of repeated dose toxicity data present in SCC(NF)P/SCCS safety evaluations of cosmetic ingredients - Mathieu Vinken; Marleen Pauwels; Gamze Ates; Manon Vivier; Tamara Vanhaecke; Vera Rogiers (Archives of Toxicology, 2012)

Characterization of spontaneous cell death in monolayer cultures of primary hepatocytes - Mathieu Vinken; Elke Decrock; Tatyana Doktorova; Eva Ramboer; Elke De Vuyst; Tamara Vanhaecke; Luc Leybaert; Vera Rogiers (Archives of Toxicology, 2011)

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

Towards an integrated in vitro strategy for repeated dose toxicity testing - Tamara Vanhaecke; Marleen Pauwels; Mathieu Vinken; Liesbeth Ceelen; Vera Rogiers (Archives of Toxicology, 2011)

Differential role of epigenetic modulators in malignant and normal stem cells: a novel tool in preclinical in vitro toxicology and clinical therapy - Sarah Snykers; Mathieu Vinken; Vera Rogiers; Tamara Vanhaecke (Archives of Toxicology, 2007)